Seven samurai - Kurosawa, Akira, 1910-1998; Motoki, Sojiro; Hashimoto, Shinobu, 1918-; Oguni, Hideo, 1904-1996; Mifune, Toshiro, 1920-1997; Shimura, Takashi, 1905-1982; Jeck, Michael C. (Criterion collection, 1998)
This epic masterpiece is about a group of 16th century samurai who are hired to defend a small Japanese village that finds itself annually raided by an army of bandits who steal the meager crops harvested by the peasants. Tired of relinquishing their food supply but woefully inept in combat skills, the villagers decide to hire a band of samurai to protect them. In addition to the primary conflict between the villagers and the bandits, much of the tale revolves around young Katsushiro's coming-of-age, both sexually and emotionally. Kikuchiyo's search for acceptance forms the other major storyline. Indeed, everyone in Seven Samurai is searching: for adventure, for experience, for freedom from their oppressors.